Diseño de una guía de aves en el parque nacional Cayambe- Coca, zona alta, Papallacta - Izurieta Chicaiza, María Alexandra (2019)
The present investigation was carried out in order to determine avifauna diversity in the Cayambe Coca National Park (PNCC), high zone, Papallacta sector; through a bird guide, so that visitors have a descriptive material of the ecological richness of these species with relevant information. For which an ecological diagnosis of the area was made, determining that the conditions and resources are adequate for the development of the birds. The place of study was divided into four zones; zone 1: virgin-antennas, zone 2: water and life trail, zone 3: bath control path, zone 4: duck lagoon; in which the vegetation, abundance of species, state of the environment, landscape, climate and altitude techniques and sampling units were applied in the same one that made tours of trails and roads already established with stops according to the need with observation times in the morning from 8:00 am to 10:00 am and in the afternoon from 4:00 pm to 6:00 pm, in the observation Directly, a tour of the 2 km open roads was carried out for two hours, four linear transects were established and a route with an average duration of 2 hours was estimated for each departure and for the count by points it remained static for a period of 1 to 2 hours for strategic places with a 360 ° turn which helped with their registration and identification.Obtaining as a result 27 species of birds; being the order passeriforme with 50% the one of greater abundance, followed of charadriiforme and apodiforme with 15% each, podicipediformes, accipriformes, anseriformes and catariformes, with 4%,in the same one that the statistical and comparative analysis of the information was applied through the abundance data of each zone and a matrix was established, which was evaluated through the statistical program estimates vr. 9 and within it, the Shannon, Chao 2, Rarefaction Curve, Accumulation Curve, Sorensen indices were calculated, since it can be concluded that by applying the species accumulation curve it was not standardized since there is no homogeneity of ecosystems, so it is advisable to follow up the study of birds in the sector considering that different sampling units are made in places with homogeneity of ecosystems to obtain a standardization of species in the same . By means of the elaboration of the field guide "REPRESENTATIVE BIRDS OF THE CAYAMBE COCA- HIGH ZONE, NATIONAL PARK", avifaunal diversity is presented. Which consists of 32 full-color pages; It contains taxonomic information, image, brief description, state of conservation and a map of distribution, which will contribute to the development of environmental interpretation activities with visitors and will promote the conservation of ecosystems and species, facilitating the development of birdlife in the sector